2014
DOI: 10.1073/pnas.1418230111
|View full text |Cite
|
Sign up to set email alerts
|

In vivo treatment of Helicobacter pylori infection with liposomal linolenic acid reduces colonization and ameliorates inflammation

Abstract: Significance The use of a liposomal formulation of linolenic acid to kill Helicobacter pylori bacteria in the stomach represents a powerful treatment option for H. pylori infection, as well as its associated gastroduodenal diseases. Because the therapeutic agent is a natural compound found in common vegetable oils, such treatment is expected to be cost-effective compared with the existing antibiotic-based anti- H. pylori … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
103
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 103 publications
(103 citation statements)
references
References 44 publications
(50 reference statements)
0
103
0
Order By: Relevance
“…AGS-NPs were suspended in water or 1X PBS and monitored for hydrodynamic sizes measured with DLS for 24 h. Herein, 1X PBS was used to simulate the pH level of stomach fluid when proton pump inhibitor (PPI) was administered in subsequent anti- H. pylori treatment. [17] In PBS, AGS-NPs maintained stable sizes comparable to those in water, indicating an enhanced colloidal stability due to the membrane coating (Figure 2C). AGS-NPs were further analyzed with Western blot for antigenic information (Figure 2D).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…AGS-NPs were suspended in water or 1X PBS and monitored for hydrodynamic sizes measured with DLS for 24 h. Herein, 1X PBS was used to simulate the pH level of stomach fluid when proton pump inhibitor (PPI) was administered in subsequent anti- H. pylori treatment. [17] In PBS, AGS-NPs maintained stable sizes comparable to those in water, indicating an enhanced colloidal stability due to the membrane coating (Figure 2C). AGS-NPs were further analyzed with Western blot for antigenic information (Figure 2D).…”
Section: Resultsmentioning
confidence: 99%
“…The study was carried out in 1X PBS to simulate the pH level in stomach when PPI was applied to block gastric acid production. [17] Without membrane coating, PLGA cores showed a prominent burst release of CLR. In contrast, burst release was minimized when release from AGS-NP(CLR) was measured.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As expected, the contents of these two compounds were decreased very significantly after ginseng administration. In addition, it was found that linolenic acid possess anti-tumorigenesis potential via gut mucosa protection and pro-inflammatory cytokine inhibition (41). In the stool samples, AOM/DSS very significantly decreased the level of linolenic acid, while its level was restored by ginseng.…”
Section: Discussionmentioning
confidence: 99%